Quantitative and Qualitative Characteristics of Boer x Local Goats Crossbred - Budiarto, Agus; Susanto, Agus; Ciptadi, Gatot; Putri, Ardyah Ramadhina Irsanti; Sunaryo, Moch. Aris (ANIMAL PRODUCTION, 2021)
The Boercang goat is a crossbred between male Boer goat and local female goat. This study was aimed to analyze the production and physical performances of Boercang goats during the weaning up to the age of one year. Thirty nine males and 37 females goats aged 3 - 12 months were used in the study. Body weight, daily weight gain, coat colour pattern, horn, ears, nose shape and birth type were recorded during study. The data obtained were calculated for the means, standard deviation (SD), and coefficient of variation (CV) and the analysis was descriptive. Student t test was performed to compare differences between groups of age and between group of sex. Field observations showed that the qualitative characteristics of Boercang such as body colour, horns, ears, and nose shape were 50 % identical with the characteristics of male Boer. The average body weight of the male Boercang goats was 23.02Â±1.56 kg whereas the female Boercang goats was 21.86Â±1.63 kg. Body weight gain was affected by age and birth type. The conclusion is that the genetic superiority of the qualitative characteristics of the Boer goats is still expressed in the offspring although it varies; for the characteristics of horns, colour patterns and ears still contribute more than 50%. The appearance of superior quantitative traits from the male Boer goat during the period of weaning up to one year of age both based on the birth type and offspring sex tends to be higher than the appearance of local goat.